2022
DOI: 10.1097/adm.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Triple Threat: Response to the Crises of COVID-19, Homelessness, and Opioid Use Disorder With a Novel Approach to Buprenorphine Delivery: A Case Series

Abstract: Objectives: In the setting of a 50% increase in opioid overdose deaths, the coronavirus disease 2019 crisis opened housing opportunities in the form of Shelter in Place (SIP) hotels to homeless San Francisco residents. Many who entered SIP hotels had opioid use disorder. In fall 2020, Community Behavioral Health Services Pharmacy partnered with SIP hotel medical staff to launch a pilot project, where on-site SIP medical providers prescribed buprenorphine (BUP) and clinical pharmacists hand-delivered BUP to SIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…While previous studies have detailed the successes of low-barrier BUP treatment models in engaging PEH, there is no literature on the effects of such models in PSH. 6,16 Given the high rate of overdose deaths occurring in those with fixed addresses and the increased risk for overdose associated with residential relocation, it is imperative that we explore methods to support individuals transitioning to living in PSH. 9,10 In this pre-and-post interventional pilot study, we found that a pharmacist-led intervention was effective in increasing BUP treatment adherence for individuals living in PSH with OUD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have detailed the successes of low-barrier BUP treatment models in engaging PEH, there is no literature on the effects of such models in PSH. 6,16 Given the high rate of overdose deaths occurring in those with fixed addresses and the increased risk for overdose associated with residential relocation, it is imperative that we explore methods to support individuals transitioning to living in PSH. 9,10 In this pre-and-post interventional pilot study, we found that a pharmacist-led intervention was effective in increasing BUP treatment adherence for individuals living in PSH with OUD.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to evaluate the impact of a pharmacist‐led outreach service in increasing BUP access for individuals residing in PSH. While previous studies have detailed the successes of low‐barrier BUP treatment models in engaging PEH, there is no literature on the effects of such models in PSH 6,16 . Given the high rate of overdose deaths occurring in those with fixed addresses and the increased risk for overdose associated with residential relocation, it is imperative that we explore methods to support individuals transitioning to living in PSH 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…OBIC began conducting virtual visits and SIP and SMSH clinicians engaged patients directly at the hotels and shelters to increase access to buprenorphine and curb morbidity and mortality from fentanyl-related overdoses. Buprenorphine was also delivered to some patients residing in the SIP hotels 29 . Directly observed dosing and/or urine drug screening (UDS) was less emphasized during our study period to reduce COVID-19 exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Buprenorphine was also delivered to some patients residing in the SIP hotels. 29 Directly observed dosing and/or urine drug screening (UDS) was less emphasized during our study period to reduce COVID-19 exposure.…”
Section: Covid-19 Impactmentioning
confidence: 99%
“…The pandemic changed patterns of substance use, disrupting the drug supply and access to medications for opiate use disorder (MOUD) in many states and hindering practices of harm reduction (such as not using alone) [24,25]. The SIP initiative similarly altered the settings in which substance use occurs but quickly fostered an innovative approach to MOUD via buprenorphine delivery [26]. Further, many of SF's methadone clinics were able to provide more take-home doses than prior to COVID.…”
Section: Substance Use Patternsmentioning
confidence: 99%